NILAI-NILAI KARAKTER DALAM PEMBELAJARAN APRESIASI SENI BERBASIS MULTIKULTURAL - Sugiarto, Eko (Fakultas Ilmu Budaya Universitas Diponegoro, 2013)
Cultural values in accordance with the substance a/education which is to educate the nation as a whole, have changed direction into a value-and-job oriented human beings. Going to school or college, a person is only to get the predicate of